Ameliorative role of dietary activated carbon against ochratoxin-A induced oxidative damage, suppressed performance and toxicological effects. (2nd January 2022) - Bhatti, Sheraz Ahmed; Khan, Muhammad Zargham; Saleemi, Muhammad Kashif; Hassan, Zahoor Ul; Khan, Ahrar
Abstract: The present study reports that dietary addition of 2.5, 5.0, 10.0 g/kg activated charcoal (AC) in broiler feed contaminated with 0.15, 0.3 and 1.0 mg/kg ochratoxin A (OTA) showed a partial reduction in intensity of mycotoxins induced toxic effects; particularly against those induced at lower doses of toxin (0.15 and 0.3 mg/kg). The protection by AC was absent against 1.0 mg/kg OTA-mediated toxicities. Moreover, AC at 10 g/kg feed also imparted toxicological effects in broiler chicken. It can be concluded that AC possess limited adsorptive potential against OTA and increasing the dose of AC may be detrimental for animal health.